The Abolition of the British Slave Trade Seen from Sierra Leone: Padraic Scanlan’s Freedom’s Debtors: British Antislavery in Sierra Leone in the Age of Revolution - Elbourne, Elizabeth (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2019)
This essay discusses the important contributions of Padraic Scanlan’s book Freedom’s Debtors: British Antislavery in Sierra Leone in the Age of Revolution, to the history of the abolition of the slave trade in the British empire. Scanlan’s innovative work emphasizes material concerns rather than altruism in explaining how policing the slave trade in West Africa and attempting to control the formerly enslaved, not least in redeploying them as soldiers, worked to the advantage of colonial administrators and British elites.  The essay examines Scanlan’s work in relation to the economic history of abolition, the history of humanitarianism, the entanglement of abolition and imperialism in West Africa, and the military history of empire, which Scanlan vitally puts back into conversation with the history of abolition.  It also asks how to include religion as a motivating force, and suggests that the book may undervalue the role of religious belief, not least among Africans.  As Scanlan’s evidence shows, the line between freedom and unfreedom was by no means sharp. Debates about the post-abolition economy were accordingly informed by anxieties about the meaning of “freedom”, as ideological beliefs informed economic conceptions.  Freedom’s Debtors demonstrates how events in Sierra Leone anticipated the fusion of humanitarianism and colonialism that was crucial to justifying empire in West Africa and underscores the vital importance of understanding abolition in terms of how it worked on the ground rather than solely how it was thought about in Britain.